(untitled) (Brazilian Journal of Oceanography, 2014)
The objective of this study was the description of the composition, abundance and density in horizontal and vertical distribution of Pleuronectiformes larvae on the southeastern Brazilian continental shelf. The samples were collected with bongo nets and a Multi Plankton Sampler (MPS), both in summer and winter 2002. A total of 352 flatfishes larvae were collected in summer and 343 in winter, representing three families and a total of 13 taxa: Paralichthyidae (Citharichthys cornutus, C. spilopterus, Citharichthys sp., Cyclopsetta chittendeni, Syacium spp., Etropus spp. and Paralichthys spp.), Bothidae (Bothus ocellatus and Monolene antillarum) and Cynoglossidae (Symphurus trewavasae, S. jenynsi, S. plagusia and S. ginsburgi). The most abundant taxa were Etropus spp., Syacium spp. and Bothus ocellatus. Etropus spp. occurred mainly as far out as the 200 m isobath and Syacium spp. from 100 m. B. ocellatus was present mainly in the oceanic zone between Ubatuba and Rio de Janeiro as from the 200 m isobath. The greatest average densities of these species occurred in the strata from 0 to 20 m depth in summer and between 20 and 40 m in winter.